Association between type of anesthesia and length of hospital stay in primary unilateral total knee arthroplasty patients: a single-center retrospective study - Xiaoqing Wang (BMC, 2021)
Abstract Objective This study explored the risk factors influencing the length of hospital stay (LOS) and establish whether the type of anesthesia is independently associated with the LOS in patients after primary unilateral total knee arthroplasty (TKA). Methods In this retrospective cohort study, 2309 patients undergoing unilateral TKA were recruited between January 2013 and June 2014 in a tertiary academic medical center in Singapore. Univariate and multivariate linear regression analyses were used to identify the independent risk factors associated with LOS. Besides, subgroup and interaction analyses were performed to evaluate the relationship between the type of anesthesia and LOS. Result In total, 2309 patients were identified. Out of these, 791 patients underwent general anesthesia, whereas 1518 patients underwent regional anesthesia. Multivariate regression analyses revealed that prolonged LOS was significantly associated with age ≥ 65 years (β = 0.48; 95% CI, 0.09–0.87; P = 0.015), diabetes mellitus (DM) (β = 0.8; 95% CI, 0.33–1.27; P = 0.001), congestive cardiac failure (CCF) (β = 4.1; 95% CI, 2.02–6.17; P < 0.001), perioperative blood transfusion (β = 5.71; 95% CI, 4.86–6.56; P < 0.001), creatinine > 2 mg/dL (β = 4.54; 95% CI, 2.46–6.62; P < 0.001), ASA status (III) (β = 1.72; 95% CI, 0.72–2.71; P = 0.001), general anesthesia (β = 0.78; 95% CI, 0.41–1.66; P < 0.001). The LOS further decreased among participants receiving regional anesthesia at advanced age (age ≥ 65 years) (β = − 1.12; 95% CI, − 1.66 to − 0.58; P < 0.001), patients with BMI ≤ 25 kg/m2 (β = − 1.92; 95% CI, − 2.73 to − 1.11; P < 0.001) or ≥ 30 kg/m2 (β = − 0.58; 95% CI, − 1.1 to − 0.06; P = 0.029). Conclusion Our findings demonstrated that age ≥ 65 years, DM, CCF, perioperative blood transfusion, creatinine > 2 mg/dL, ASA status (III), general anesthesia are associated with a prolonged LOS after primary TKA. Elderly patients (age ≥ 65 years) and patients with BMI ≤ 25 kg/m2 or ≥ 30 kg/m2 receiving regional anesthesia have a further reduced LOS. Therefore, when TKA is performed, priority for regional anesthesia is given to the elderly patients (age ≥ 65 years old) and those with BMI ≤ 25 kg/m2 or ≥ 30 kg/m2.